6(m+2)+14=4+3(m-1)

Simple and best practice solution for 6(m+2)+14=4+3(m-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(m+2)+14=4+3(m-1) equation:


Simplifying
6(m + 2) + 14 = 4 + 3(m + -1)

Reorder the terms:
6(2 + m) + 14 = 4 + 3(m + -1)
(2 * 6 + m * 6) + 14 = 4 + 3(m + -1)
(12 + 6m) + 14 = 4 + 3(m + -1)

Reorder the terms:
12 + 14 + 6m = 4 + 3(m + -1)

Combine like terms: 12 + 14 = 26
26 + 6m = 4 + 3(m + -1)

Reorder the terms:
26 + 6m = 4 + 3(-1 + m)
26 + 6m = 4 + (-1 * 3 + m * 3)
26 + 6m = 4 + (-3 + 3m)

Combine like terms: 4 + -3 = 1
26 + 6m = 1 + 3m

Solving
26 + 6m = 1 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
26 + 6m + -3m = 1 + 3m + -3m

Combine like terms: 6m + -3m = 3m
26 + 3m = 1 + 3m + -3m

Combine like terms: 3m + -3m = 0
26 + 3m = 1 + 0
26 + 3m = 1

Add '-26' to each side of the equation.
26 + -26 + 3m = 1 + -26

Combine like terms: 26 + -26 = 0
0 + 3m = 1 + -26
3m = 1 + -26

Combine like terms: 1 + -26 = -25
3m = -25

Divide each side by '3'.
m = -8.333333333

Simplifying
m = -8.333333333

See similar equations:

| 2y+6y+9-5y=24 | | 3e+20=10e+6 | | 90=2(q+25) | | Z=.5a-.5b(6-.2z) | | 3h+1=13 | | 10x-2y=11 | | 2(u-9)-9=-6(-2u+7)-u | | r+10=-9r-10 | | -9y+1=-y+25 | | -5y=-7y-8 | | y-25=9y-1 | | 13z-15z-4=0 | | 10q=9q-4 | | 60-12x=9-6x | | p=15-3Q | | 6x-9y-7y+11x+8= | | -2(2t+4)=20 | | 4X+X-20=180 | | -4j+9=7j+9 | | 2x+3(32.5-0.5x)=105 | | 3^x=1/81 | | 7*​x^​2-​x^​1/​3 | | -t=-9-t | | 8v+48=2(v-6) | | 1/3=x/3(3/5) | | 5*a+3*b+10=147 | | 7/3×p/3 | | 4-9f=-4-9f | | 2(11+-1y)+2(0)=22 | | 5/8=x/(1/7) | | 3(y+3)=7y-7 | | 3(11+-1y)+3y=33 |

Equations solver categories